Case Report: A Rehabilitation Practice Report During ICU Management for a Patient With Multiple Disabilities Due to COVID-19 Pneumonia and COPD - Kinoshita, Tokio; Kouda, Ken; Umemoto, Yasunori; Yasuoka, Yoshinori; Minoshima, Yuta; Mikami, Yukio; Nishimura, Yukihide; Miyamoto, Kyohei; Kato, Seiya; Tajima, Fumihiro (Frontiers in Medicine, 2021)
Patients with severe coronavirus disease (COVID-19) and admitted to intensive care units (ICUs) are at high risk of developing ICU-acquired weakness (ICU-AW) and disuse syndrome. Their medical management may include prolonged deep sedation for pulmonary protection and ventilator management. We also target early mobilization for patients with COVID-19 under deep sedation and ventilator management. We report a case of a 71-year-old male with chronic obstructive pulmonary disease (COPD) and COVID-19 pneumonia. Early rehabilitation therapy was commenced in the ICU while the patient was under deep sedation. His activities of daily living eventually improved to where he could independently transfer to the toilet without respiratory distress. Patients with severe COVID-19 who require mechanical ventilation are at risk of muscle weakness and exercise intolerance. These patients require rehabilitation therapy, beginning in the acute phase of illness, to recover their physical function. Although they require validation in a larger cohort, our results suggest that patients with COPD and COVID-19 pneumonia should be rehabilitated concurrently with status-driven changes in respiratory management.